Codification Of Islamic Family Law In Malaysia: The Contending Legal Intricacies - Yusuf Abdul Azeez; Luqman Zakariyah; Ahmad Zaki Salleh; Syahirah Abdul Shukor (Science International, Lahore Pakistan, 2024)
The Predominance School of Law in Malaysia today is the Madhhab Shafi‘i. However, several criticisms have been leveled against the exclusive reliance on this School of Law on the argument that it gives room for unnecessary restrictions of freedom, considers some tribes to be special and treats the females unfairly, especially in the matters of Islamic family laws related to polygamy, matrimonial property and divorce. The Religious Departments at various levels in Malaysia were also accused of ignoring this legal conundrum, like those inherited from the polygamous and divorce laws, which as perceived by many, could not only lead to exploitation of the women by irresponsible men but may also favours the husbands in matters of adjudication. This paper attempts to unveil the potential legal intricacies inherited from the Malaysian Family Law through a critical examination of the contending issues raised against it. Thus, such a kind of examination is not only expected to uncover the mix methods used in codifying these laws but, also, will appraise the extent of their compatibility or otherwise to the maqāsīd al-Sharīʿah (the objectives of Islamic Law) and the contemporary International Human Rights Law. In doing so, suggestion on how those laws could be improved upon in order to be in conformity with the objects of Islamic law and the human rights standard will be put forth.